2019
DOI: 10.1111/pce.13547
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid‐dependent histone demethylation during postgermination growth arrest in Arabidopsis

Abstract: After germination, seedlings undergo growth arrest in response to unfavourable conditions, a critical adaptation enabling plants to survive harsh environments. The plant hormone abscisic acid (ABA) plays a key role in this arrest. To arrest growth, ABA‐dependent transcription factors change gene expression patterns in a flexible and reversible manner. Although the control of gene expression has important roles in growth arrest, the epigenetic mechanisms in the response to ABA are not fully understood. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 75 publications
3
44
0
Order By: Relevance
“…There may also be multiple other participants in this process. For example, JMJ30, a histone demethylase, is able to block the inhibition mediated by the H3 lysine 27 trimethylation epigenetic mark (H3K27me3) at the promoter of SnRK2.8 and hence release the suppression of ABI3 to promote PGG arrest (Wu et al 2019). Recently, it was reported that RAF22 in Arabidopsis acts as a negative regulator of PGG arrest that is independent of the canonical ABI5‐mediated ABA cascade (Hwang et al 2018).…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…There may also be multiple other participants in this process. For example, JMJ30, a histone demethylase, is able to block the inhibition mediated by the H3 lysine 27 trimethylation epigenetic mark (H3K27me3) at the promoter of SnRK2.8 and hence release the suppression of ABI3 to promote PGG arrest (Wu et al 2019). Recently, it was reported that RAF22 in Arabidopsis acts as a negative regulator of PGG arrest that is independent of the canonical ABI5‐mediated ABA cascade (Hwang et al 2018).…”
Section: Abscisic Acid In Seed Developmentmentioning
confidence: 99%
“…BES1 can directly bind to the promoter region of ABI3 and then recruit histone deacetylase HDA19 to deacetylate H3. Additionally, histone modifications are also involved in the fine‐tuning of SnRK2.8 via ABI3 (Wu et al 2019). Abscisic acid treatment induces the expression of ABI3 , and then ABI3 binds to the RY motif in the histone demethylase JMJ30 gene promoter to activate its expression.…”
Section: Epigenetic Regulation Of Aba Responsesmentioning
confidence: 99%
“…Abscisic acid treatment induces the expression of ABI3 , and then ABI3 binds to the RY motif in the histone demethylase JMJ30 gene promoter to activate its expression. JMJ30 can remove the repressive marker H3K27me3 from the promoter region of SnRK2.8 , and hence activates SnRK2.8 expression; SnRK2.8 kinase, in turn, activates the expression of ABI3 (Wu et al 2019).…”
Section: Epigenetic Regulation Of Aba Responsesmentioning
confidence: 99%
“…Indeed, the B3 domain transcription factor ABI3, APETALA2-type transcription factor ABI4, and bZIP transcription factor ABI5 functioned genetically in the downstream of AtNDX. ABA-mediated growth arrest in A. thaliana was controlled by histone demethylases [96]. The expression of ABI3 increased in ndx, but AtNDX could not directly bind to ABI3 [95].…”
Section: Regulation Mechanism Of Lncrnas In Gene Transcriptionmentioning
confidence: 98%